A main-chain polysiloxane-acrylic metal salt resin, a preparation method and application thereof

CN123003797APending Publication Date: 2026-10-30SANYA INST OF OCEANOGRAPHY OCEAN UNIV OF CHINA +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611350624.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明在丙烯酸金属盐树脂基础上,于碳碳主链中引入疏水性聚硅氧烷链段,旨在降低丙烯酸金属盐树脂的自抛光速率,同时有效克服因聚硅氧烷结构与碳碳主链极性差异所引发的微相分离问题

Benefits of technology

[0032]与现有技术相比,本发明的有益效果是:本发明将含丙烯酸酯基础单体、甲基丙烯酸酯单体、功能性单体和乙烯基硅油共聚,制备了线性结构的聚硅氧烷-丙烯酸金属盐树脂,涂覆在基材上形成涂层,具有平整的粗糙度和自抛光性能,所得海洋防污涂层的表面粗糙度小,最大可降低涂层的水解质量损失 40.56%,在天然海水环境中具有长达 270 天以上的防污期效,显示出其在海洋防污材料领域良好的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003797A_ABST
    Figure CN123003797A_ABST
Patent Text Reader

Abstract

The application provides a main chain type polysiloxane-acrylic metal salt resin and a preparation method and application thereof, and relates to the field of marine antifouling polymer materials.The application introduces a hydrophobic polysiloxane segment into a carbon-carbon main chain on the basis of an acrylic metal salt resin, aims to reduce the self-polishing rate of the acrylic metal salt resin, effectively overcomes the micro-phase separation problem caused by the polarity difference between the polysiloxane structure and the carbon-carbon main chain, and successfully prepares the main chain type polysiloxane-acrylic metal salt resin.The main chain type polysiloxane-acrylic metal salt resin is used for preparing a marine antifouling coating, has a self-polishing performance, the obtained marine antifouling coating has small surface roughness, and has an antifouling effect of more than 9 months in a natural seawater environment, and shows a good application prospect in the field of marine antifouling materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of marine antifouling polymer materials, and in particular to a main-chain polysiloxane-acrylate metal salt resin, its preparation method, and its application. Background Technology

[0002] With the continuous expansion of marine engineering fields such as deep-sea exploration and offshore wind power, the comprehensive performance requirements for marine antifouling materials in terms of environmental protection, long-term effectiveness, and broad-spectrum compatibility are becoming increasingly stringent. Traditional antifouling coatings can no longer meet the long-term service requirements of modern marine equipment under extreme operating conditions. Marine biofouling has become one of the major bottlenecks restricting the development of the marine economy.

[0003] Among numerous environmentally friendly antifouling materials, environmentally friendly self-polishing antifouling coatings from Wuxi, with acrylic metal salt resins as the key base material, are an important category. Acrylic metal salt resins, due to their excellent ion exchange and hydrolysis properties, have become the primary choice for antifouling coating matrix resins. However, existing acrylic metal salt resins still suffer from insufficient hydrolytic stability in complex marine environments, a "ceiling effect" in antifouling performance, and relatively limited functionality, making further breakthroughs difficult. They can only provide basic protection and cannot meet the diverse needs of antifouling scenarios or the urgent requirements of modern marine equipment for long-lasting, multi-functional protection.

[0004] Therefore, based on the trend of antifouling coatings developing towards environmental friendliness, long-term stability, and multifunctionality, the development of novel acrylic metal salt resins with controllable hydrolysis rates and multiple antifouling mechanisms has become an urgent task. To this end, this invention utilizes the copolymerization of vinyl silicone oil and acrylate monomers to prepare a main-chain polysiloxane-acrylic metal salt resin, aiming to control the hydrolysis rate of the acrylic metal salt resin, achieve long-term stable polishing of the coating, and thus improve the long-term service performance of the antifouling coating. Summary of the Invention

[0005] In view of this, the present invention proposes a main-chain polysiloxane-acrylic metal salt resin, its preparation method and application.

[0006] This invention introduces hydrophobic polysiloxane segments into the carbon-carbon backbone of an acrylic metal salt resin, aiming to reduce the self-polishing rate of the resin and effectively overcome the microphase separation problem caused by the polarity difference between the polysiloxane structure and the carbon-carbon backbone. The resulting antifouling coating has low surface roughness and exhibits antifouling performance for over 9 months in a real marine environment, demonstrating its promising application prospects in the field of marine antifouling materials.

[0007] The technical solution of the present invention is implemented as follows: a main-chain polysiloxane-acrylate metal salt resin, the general structural formula of which is shown in formula (I): (I); In the formula, the general structural formula of M is shown in formula (II): (II); R1 is H or CH3; R2 is -C4H8N, -C5H9O, -C6H 13 O2、‐C7H 13 -C8H9O or -C 10 H 17 ; R3 is -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -CH2CH(CH3)2, -C(CH3)3, -CH2CH2OH, -CH2CH(CH3)OH , -(CH2)3CH3, -(CH2)4CH3, -(CH2)5CH3, -(CH2)6CH3, -(CH2)7CH3, -(CH2)8CH3, (CH2)9CH3, (CH2) 10 CH3, (CH2) 11 CH3, C8H 17 Or (CH2) 17 CH3; R4 is H or CH3; X is a Zn, Cu, Fe, Ca, or Mg metal ion; R5 is the anion of benzoic acid, naphthenic acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, rosin acid, proline, leucine, phenylalanine or arginine, dimer rosin acid, disproportionated rosin acid, salicylic acid or p-chlorobenzoic acid. R6 is H or CH3; x, y, z, l, and i are all integers, where x = 100~500, y = 50~500, z = 100~1000, l = 50~300, and i = 50~5000.

[0008] Furthermore, the main-chain polysiloxane-acrylate metal salt resin has the general structural formula shown in formula (1): (1); In the formula, the general structural formula of M is shown in formula (II); x, y, z, l, m, and n are all integers, x = 100~500, y = 50~500, z = 100~1000, l = 50~300, m = 0~50, and n = 20~200; Y represents an organic acid, which is one of benzoic acid, rosin, or naphthenic acid.

[0009] The present invention provides a method for preparing a main-chain polysiloxane-acrylic metal salt resin, comprising the following steps: S1. Mix acrylate base monomers, acrylic acid, methacrylic acid, acrylamide, and functional acrylate monomers in a molar ratio of (50-150):(0-50):(0-40):(0-40):(1-10); then add 5%-40% (preferably 5%-10%) of terminal vinyl silicone oil, based on the total mass of all the monomers, to prepare monomer mixture M1; subsequently, weigh 0.8%-3.2% (by weight of the monomer mixture) of initiator for later use. S2. Mix the first part M1 and the first part initiator to obtain monomer mixture M2; The second part M1 and the second part of the initiator are mixed to obtain monomer mixture M3; S3. In a protective gas atmosphere, monomer mixture M2, monomer mixture M3, the third part initiator, chain transfer agent and solvent are reacted to obtain acrylic acid prepolymer; S4. In a protective gas atmosphere, acrylic prepolymer, metal compound, organic acid and solvent are mixed and reacted to obtain main-chain polysiloxane-acrylic metal salt self-polishing resin.

[0010] In this invention, the main role of acrylic acid and methacrylic acid in the preparation of acrylic acid prepolymer is to polymerize into a prepolymer with a large number of carboxyl groups in the side chain, and participate in the dehydration reaction with the metal compound in step S4.

[0011] Furthermore, in step S1, the preferred molar ratio of acrylate base monomer, acrylic acid, methacrylic acid, acrylamide, and functional acrylate monomer is (50-150): (2-6): (5-10): (5-10): (2-4).

[0012] Furthermore, in step S1, the acrylate base monomer is one or more of butyl acrylate, ethyl acrylate, methyl acrylate, isooctyl acrylate, lauryl acrylate, and octadecyl acrylate; preferably one or more of butyl acrylate, ethyl acrylate, and lauryl acrylate. The main function of the acrylate base monomer is to change the length of the side chain and adjust the viscosity of the prepolymer during the preparation of acrylic prepolymer, so as to facilitate the subsequent preparation of hydroxyl-containing silane acrylate / metal salt acrylate resin with excellent viscosity.

[0013] Furthermore, in step S1, the functional acrylate monomer is one or more of 4-acryloylmorpholine, isobornyl acrylate, cyclohexyl methacrylate, tetrahydrofurfuryl acrylate, ethoxyethoxyethyl acrylate, and 2-phenoxyethyl acrylate.

[0014] Furthermore, in step S1, the viscosity of the terminal vinyl silicone oil is 30 to 10000 mPa·s, preferably 100 to 2000 mPa·s, which provides better structural stability when copolymerized with carbon-carbon chains.

[0015] Further, in step S1, the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, tert-butyl peroxide, methyl ethyl ketone peroxide, ammonium persulfate, and potassium persulfate; preferably one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, ammonium persulfate, and potassium persulfate, more preferably one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, ammonium persulfate, and potassium persulfate; the main function of the initiator in preparing acrylic prepolymer is to decompose into active species and initiate monomer polymerization; too little initiator will lead to incomplete polymerization of acrylic resin and low conversion rate, while too much initiator will lead to high viscosity and short molecular chains of acrylic resin, which is not conducive to resin adhesion and film formation.

[0016] Further, in steps S2 and S3, the first part M1 accounts for 10% to 30% of the total mass of M1, preferably 10% to 20%, more preferably 12% to 18%, and more preferably 14% to 16%; the mass ratio of the total mass of the first part initiator, the second part initiator, and the third part initiator to the mass of M1 is 0.8 to 3.2:100, preferably 1.0 to 3.0:100, and more preferably 1.5 to 2.5:100; the first part initiator accounts for 15% to 30% of the total mass of the initiator, preferably 18% to 26%, and more preferably 20% to 25%; the second part initiator accounts for 50% to 70% of the total mass of the initiator, preferably 55% to 65%, and more preferably 60%.

[0017] Furthermore, in step S3, the monomer mixture M2, chain transfer agent and solvent are first mixed and reacted to obtain the first reaction product. Then the first reaction product is mixed with the monomer mixture M3 and reacted to obtain the second reaction product. Finally, the second reaction product is mixed with the third initiator and reacted to obtain the main-chain polysiloxane-acrylic acid prepolymer.

[0018] Furthermore, in step S3, M3 is divided into 9 to 19 parts, preferably 10 to 18 parts, and more preferably 12 to 16 parts; one part is added at intervals of 10 to 30 minutes, preferably 12 to 18 minutes, and more preferably 14 to 16 minutes; the purpose of adding M3 in batches is to avoid agglomeration or explosion caused by excessive local temperature due to excessive single addition. The purpose of synthesizing acrylic acid prepolymer is to generate polymers with a large number of carboxyl groups in the side chains through free radical polymerization reaction, providing a precursor for the next step of preparing hydroxyl-containing silane acrylate / metal salt acrylate resin.

[0019] Further, in step S3, the mass ratio of solvent, chain transfer agent, and M1 is (75~150):(0.3~2):100; the temperature of the first reaction is 75~110℃, preferably 80~105℃, more preferably 85~100℃; the time of the first reaction is 15~45min, preferably 20~40min, more preferably 25~35min; if the temperature of the first reaction is lower than 75℃, it will be detrimental to initiating monomer mixing; if the temperature of the first reaction is higher than 110℃, it will lead to the deactivation of active species.

[0020] The temperature of the second reaction is 80~95℃, preferably 83~92℃, and more preferably 85~90℃; in the second reaction, after all M3 is added, the reaction time is 10~30min, preferably 10~20min, and more preferably 15min.

[0021] The temperature of the third reaction is 80~95℃, preferably 83~92℃, and more preferably 85~90℃; the time of the third reaction is 2.5~3.5h, preferably 2.7~3.3h, and more preferably 2.8~3.0h.

[0022] Furthermore, in step S3, the chain transfer agent is one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, and aliphatic thiols; preferably n-dodecyl mercaptan and / or tert-dodecyl mercaptan, more preferably tert-dodecyl mercaptan; the main function of the chain transfer agent is to cause free radical transfer of the chain-growing free radicals during the preparation of acrylic acid prepolymer, thereby controlling the molecular weight of acrylic acid prepolymer; if the amount of chain transfer agent is lower than the range defined in this invention, it will lead to difficulty in terminating free radical polymerization; if the amount of chain transfer agent is higher than the range defined in this invention, it will lead to a decrease in polymer viscosity and excessively short molecular chains.

[0023] Furthermore, in step S4, the metal compound is one or more of zinc oxide, copper oxide, magnesium oxide, calcium oxide, zinc hydroxide, copper hydroxide, iron hydroxide, magnesium hydroxide, and calcium hydroxide, preferably one or more of zinc oxide, copper oxide, magnesium oxide, zinc hydroxide, copper hydroxide, magnesium hydroxide, and calcium hydroxide, and more preferably one or more of zinc oxide, copper oxide, magnesium oxide, copper hydroxide, and calcium hydroxide.

[0024] Further, in step S4, the organic acid is one or more of benzoic acid, naphthenic acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, rosin acid, proline, leucine, phenylalanine, arginine, dimer rosin acid, disproportionated rosin acid, salicylic acid, furoic acid, and p-chlorobenzoic acid, preferably one or more of benzoic acid, naphthenic acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, leucine, phenylalanine, dimer rosin acid, disproportionated rosin acid, salicylic acid, furoic acid, and p-chlorobenzoic acid, and more preferably one or more of benzoic acid, naphthenic acid, lauric acid, acetic acid, propionic acid, butyric acid, phenylalanine, disproportionated rosin acid, salicylic acid, furoic acid, and p-chlorobenzoic acid.

[0025] Furthermore, in steps S3 and S4, the protective gas is selected from any one of nitrogen, argon, helium, and neon; preferably nitrogen or argon, and more preferably nitrogen.

[0026] Furthermore, in steps S3 and S4, the solvent is selected from one or more of toluene, xylene, n-butanol, butyl acetate, ethyl acetate, cyclohexanone, and methyl isobutyl ketone; preferably one or more of toluene, xylene, n-butanol, cyclohexanone, and methyl isobutyl ketone, and more preferably one or more of toluene, xylene, cyclohexanone, and methyl isobutyl ketone. Excessive solvent usage will not only cause air pollution but also waste solvent; insufficient solvent usage will result in poor solubility of the system, high viscosity of hydroxyl-containing silicone acrylate / acrylic metal salt resin, which is not conducive to heat transfer in the system and affects the reaction process; during the coating curing stage, the amount of solvent will also affect the drying rate and leveling properties of the coating.

[0027] Further, in step S4, the molar ratio of the metal compound to the organic acid is 0.5~1:1, preferably 0.7~0.9:1, and more preferably 0.8:1. The purpose is to ensure that the two react fully as much as possible, as excessive content will result in a large amount of metal compound remaining in the polymer solution. The total molar amount of the metal compound and the organic acid is 1~2 times the total molar amount of acrylic acid and methacrylic acid in step S1, preferably 1.2~1.8 times, and more preferably 1.4~1.6 times. The purpose is to ensure that the dehydration condensation reaction proceeds fully. The mass ratio of the total mass of the metal compound and the organic acid to the mass of the solvent is 1:1~2, preferably 1:1.2~1.8, and more preferably 1:1.4~1.6. The reaction temperature is 75~110℃, preferably 80~105℃, and more preferably 85~100℃. The reaction time is 3~10h, preferably 4~9h, and more preferably 5~8h.

[0028] Furthermore, in step S4, the acrylic prepolymer is cooled to 70°C or below, preferably ≤65°C, and more preferably ≤60°C, before participating in the reaction. The purpose is to prevent excessively high temperatures from causing violent reactions when other substances are added.

[0029] The present invention relates to the application of main-chain polysiloxane-acrylic metal salt resin in marine antifouling.

[0030] This invention provides a marine antifouling polymer composition containing the main-chain polysiloxane-acrylate metal salt resin of this invention.

[0031] Furthermore, the present invention provides a marine antifouling coating containing the main chain-type polysiloxane-acrylate metal salt resin of the present invention.

[0032] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention copolymerizes acrylate-based monomers, methacrylate monomers, functional monomers and vinyl silicone oil to prepare a linear polysiloxane-acrylate metal salt resin, which is then coated on a substrate to form a coating with smooth roughness and self-polishing properties. The resulting marine antifouling coating has low surface roughness and can reduce the hydrolytic mass loss of the coating by up to 40.56%. It has an antifouling effect of more than 270 days in natural seawater environment, showing its good application prospects in the field of marine antifouling materials. Attached Figure Description

[0033] Figure 1 Infrared spectra of main-chain polysiloxane-zinc acrylate resins prepared in Examples 1-4 for comparison.

[0034] Figure 2 Thermogravimetric spectra of main-chain polysiloxane-zinc acrylate resins prepared in Examples 1-4 are shown for comparison.

[0035] Figure 3 XPS curves of the main-chain polysiloxane-zinc acrylate resin prepared in Example 1.

[0036] Figure 4 The fine C1s spectrum of the main-chain polysiloxane-zinc acrylate resin prepared in Example 1 is shown.

[0037] Figure 5 The fine O1s spectrum of the main-chain polysiloxane-zinc acrylate resin prepared in Example 1 is shown.

[0038] Figure 6 The fine N1s spectrum of the main-chain polysiloxane-zinc acrylate resin prepared in Example 1 is shown.

[0039] Figure 7 The fine Si2p spectrum of the main-chain polysiloxane-zinc acrylate resin prepared in Example 1 is shown.

[0040] Figure 8 The fine Zn2p spectrum of the main-chain polysiloxane-zinc acrylate resin prepared in Example 1 is shown.

[0041] Figure 9 This is a graph showing the mass loss of coatings prepared from main-chain polysiloxane-zinc acrylate resins in comparative examples 1-4 after immersion in natural seawater for 35 days.

[0042] Figure 10 The changes in surface morphology and roughness of coatings prepared from main-chain polysiloxane-zinc acrylate resins in Comparative Examples 1-4 after immersion in natural seawater for 7 days are shown.

[0043] Figure 11 The results are from a sea test conducted in the Yellow Sea off Qingdao, Shandong Province, on coatings prepared from the main-chain polysiloxane-zinc acrylate resins of comparative examples 1-4. Detailed Implementation

[0044] Unless otherwise specified, the experimental methods used in the embodiments of this invention are conventional methods; Unless otherwise specified, all materials and reagents used in the embodiments of this invention are commercially available.

[0045] The acrylate monomers used in the embodiments of this invention were purchased from Qingdao Datang Chemical Co., Ltd. or Huai'an Guoyao Chemical Reagent Co., Ltd.; acrylic acid and methacrylic acid were both purchased from Qingdao Datang Chemical Co., Ltd.; the viscosity of the vinyl-terminated silicone oil was approximately 100 mPa·s, product model VDV100, and it was purchased from Huangshan Qiangli Chemical Co., Ltd.; the initiator was purchased from Tianjin Damao Chemical Reagent Partnership (Limited Partnership) (formerly known as Tianjin Damao Chemical Reagent Factory) or Tianjin Hedong East District Hongyan Reagent Factory; the chain transfer agent was purchased from Huai'an Guoyao Chemical Reagent Co., Ltd.; the organic acid was purchased from Huai'an Guoyao Chemical Reagent Co., Ltd. or Shanghai Aibi Chemical Reagent Co., Ltd.; and the solvent was purchased from Huai'an Guoyao Chemical Reagent Co., Ltd. or Tianjin Guangcheng Chemical Reagent Co., Ltd.

[0046] This invention provides a main-chain polysiloxane-acrylate metal salt resin, the general structural formula of which is shown in formula (I): (I); In the formula, the general structural formula of M is shown in formula (II): (II); R1 is H or CH3; R2 is -C4H8N, -C5H9O, -C6H 13 O2、‐C7H 13 -C8H9O or -C 10 H 17 ; R3 is -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -CH2CH(CH3)2, -C(CH3)3, -CH2CH2OH, -CH2CH(CH3)OH , -(CH2)3CH3, -(CH2)4CH3, -(CH2)5CH3, -(CH2)6CH3, -(CH2)7CH3, -(CH2)8CH3, (CH2)9CH3, (CH2) 10 CH3, (CH2) 11 CH3, C8H 17 Or (CH2) 17 CH3; R4 is H or CH3; X is a Zn, Cu, Fe, Ca or Mg metal ion; R5 is the anion of benzoic acid, naphthenic acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, rosin acid, proline, leucine, phenylalanine or arginine, dimer rosin acid, disproportionated rosin acid, salicylic acid or p-chlorobenzoic acid. R6 is H or CH3; x, y, z, l, and i are all integers, where x = 100~500, y = 50~500, z = 100~1000, l = 50~300, and i = 50~5000.

[0047] The present invention provides a method for preparing a main-chain polysiloxane-acrylic metal salt resin, comprising the following steps: S1. Mix acrylate base monomers, acrylic acid, methacrylic acid, acrylamide, and functional acrylate monomers in a molar ratio of (50-150):(0-50):(0-40):(0-40):(1-10); then add 5%-40% (preferably 5%-10%) of terminal vinyl silicone oil, based on the total mass of all the monomers, to prepare monomer mixture M1; subsequently, weigh 0.8%-3.2% (by weight of the monomer mixture) of initiator for later use. S2. Mix the first part M1 and the first part initiator to obtain monomer mixture M2; The second part M1 and the second part of the initiator are mixed to obtain monomer mixture M3; S3. In a protective gas atmosphere, monomer mixture M2, monomer mixture M3, the third part initiator, chain transfer agent and solvent are reacted to obtain acrylic acid prepolymer; S4. In a protective gas atmosphere, acrylic prepolymer, metal compound, organic acid and solvent are mixed and reacted to obtain main-chain polysiloxane-acrylic metal salt self-polishing resin.

[0048] In this invention, in step S1, the preferred molar ratio of acrylate base monomer, acrylic acid, methacrylic acid, acrylamide, and functional acrylate monomer is (50-150): (2-6): (5-10): (5-10): (2-4).

[0049] In this invention, in step S1, the acrylate base monomer is one or more of butyl acrylate, ethyl acrylate, methyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate; preferably one or more of butyl acrylate, ethyl acrylate and lauryl acrylate.

[0050] In this invention, in step S1, the functional acrylate monomer is one or more of isobornyl acrylate, cyclohexyl methacrylate, tetrahydrofurfuryl acrylate, ethoxyethoxyethyl acrylate, 2-phenoxyethyl acrylate, and 4-acryloylmorpholine.

[0051] In this invention, in step S1, the viscosity of the terminal vinyl silicone oil is 30 to 10000 mPa·s, preferably 100 to 2000 mPa·s.

[0052] In this invention, in step S1, the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, tert-butyl peroxide, methyl ethyl ketone peroxide, ammonium persulfate, and potassium persulfate; preferably one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, ammonium persulfate, and potassium persulfate, and more preferably one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, ammonium persulfate, and potassium persulfate.

[0053] In this invention, in steps S2 and S3, the first part M1 accounts for 10% to 30% of the total mass of M1, preferably 10% to 20%, more preferably 12% to 18%, and more preferably 14% to 16%; the mass ratio of the total mass of the first part initiator, the second part initiator, and the third part initiator to the mass of M1 is 0.8 to 3.2:100, preferably 1.0 to 3.0:100, and more preferably 1.5 to 2.5:100; the first part initiator accounts for 15% to 30% of the total mass of the initiator, preferably 18% to 26%, and more preferably 20% to 25%; the second part initiator accounts for 50% to 70% of the total mass of the initiator, preferably 55% to 65%, and more preferably 60%.

[0054] In this invention, in step S3, the monomer mixture M2, the chain transfer agent and the solvent are first mixed and then reacted to obtain the first reaction product. The first reaction product is then mixed with the monomer mixture M3 and then reacted to obtain the second reaction product. Finally, the second reaction product is mixed with the third initiator and then reacted to obtain the main-chain polysiloxane-acrylic acid prepolymer.

[0055] In this invention, in step S3, M3 is divided into 9 to 19 parts, preferably 10 to 18 parts, and more preferably 12 to 16 parts; one part is added at intervals of 10 to 30 minutes, preferably 12 to 18 minutes, and more preferably 14 to 16 minutes.

[0056] In this invention, the mass ratio of solvent, chain transfer agent and M1 in step S3 is (75~150):(0.3~2):100; the temperature of the first reaction is 75~110℃, preferably 80~105℃, more preferably 85~100℃; the time of the first reaction is 15~45min, preferably 20~40min, more preferably 25~35min.

[0057] The temperature of the second reaction is 80~95℃, preferably 83~92℃, and more preferably 85~90℃; in the second reaction, after all M3 is added, the reaction time is 10~30min, preferably 10~20min, and more preferably 15min.

[0058] The temperature of the third reaction is 80~95℃, preferably 83~92℃, and more preferably 85~90℃; the time of the third reaction is 2.5~3.5h, preferably 2.7~3.3h, and more preferably 2.8~3.0h.

[0059] In this invention, in step S3, the chain transfer agent is one or more of n-dodecyl mercaptan, tertiary dodecyl mercaptan, and aliphatic thiols; preferably n-dodecyl mercaptan and / or tertiary dodecyl mercaptan, and more preferably tertiary dodecyl mercaptan.

[0060] In this invention, in step S4, the metal compound is one or more of zinc oxide, copper oxide, magnesium oxide, calcium oxide, zinc hydroxide, copper hydroxide, iron hydroxide, magnesium hydroxide, and calcium hydroxide, preferably one or more of zinc oxide, copper oxide, magnesium oxide, zinc hydroxide, copper hydroxide, magnesium hydroxide, and calcium hydroxide, and more preferably one or more of zinc oxide, copper oxide, magnesium oxide, copper hydroxide, and calcium hydroxide.

[0061] In this invention, in step S4, the organic acid is one or more of benzoic acid, naphthenic acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, rosin acid, proline, leucine, phenylalanine, arginine, dimer rosin acid, disproportionated rosin acid, salicylic acid, furoic acid, and p-chlorobenzoic acid. Preferably, it is one or more of benzoic acid, naphthenic acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, leucine, phenylalanine, dimer rosin acid, disproportionated rosin acid, salicylic acid, furoic acid, and p-chlorobenzoic acid. More preferably, it is one or more of benzoic acid, naphthenic acid, lauric acid, acetic acid, propionic acid, butyric acid, phenylalanine, disproportionated rosin acid, salicylic acid, furoic acid, and p-chlorobenzoic acid.

[0062] In this invention, in steps S3 and S4, the protective gas is selected from any one of nitrogen, argon, helium and neon; preferably nitrogen or argon, and more preferably nitrogen.

[0063] In this invention, in steps S3 and S4, the solvent is selected from one or more of toluene, xylene, n-butanol, butyl acetate, ethyl acetate, cyclohexanone, and methyl isobutyl ketone; preferably one or more of toluene, xylene, n-butanol, cyclohexanone, and methyl isobutyl ketone, and more preferably one or more of toluene, xylene, cyclohexanone, and methyl isobutyl ketone.

[0064] In this invention, in step S4, the molar ratio of the metal compound to the organic acid is 0.5~1:1, preferably 0.7~0.9:1, and more preferably 0.8:1; the total molar amount of the metal compound and the organic acid is 1~2 times the total molar amount of acrylic acid and methacrylic acid in step S1, preferably 1.2~1.8 times, and more preferably 1.4~1.6 times; the mass ratio of the total mass of the metal compound and the organic acid to the mass of the solvent is 1:1~2, preferably 1:1.2~1.8, and more preferably 1:1.4~1.6; the reaction temperature is 75~110℃, preferably 80~105℃, and more preferably 85~100℃; the reaction time is 3~10h, preferably 4~9h, and more preferably 5~8h.

[0065] In this invention, in step S4, the acrylic prepolymer is cooled to 70°C or below, preferably ≤65°C, and more preferably ≤60°C, before participating in the reaction. The purpose is to prevent the temperature from being too high, which could cause a violent reaction when other substances are added.

[0066] Example 1 S1. Butyl acrylate, ethyl acrylate, acrylic acid, acrylamide, lauryl acrylate, and 4-acryloylmorpholine are mixed in a molar ratio of 80:40:40:15:18:2 to obtain a mixed monomer; vinyl-terminated silicone oil (VDV100) is mixed with the mixed monomer to prepare a monomer mixture (M1), with the amount of vinyl-terminated silicone oil (VDV100) added being 5 wt% of the total mass of the mixed monomer; 1.0% of azobisisobutyronitrile (initiator) based on the weight of the monomer mixture is weighed and set aside. S2. The monomer mixture M1 is divided into two parts, namely Part 1 M1 and Part 2 M1, with Part 1 M1 accounting for 10% of the total mass of M1. The initiator is divided into three parts, namely Part 1 initiator, Part 2 initiator, and Part 3 initiator, with Part 1 initiator accounting for 15% of the total mass of initiator and Part 2 initiator accounting for 65% of the total mass of initiator. 10 wt% of the monomer mixture (i.e., Part 1 M1) and 15 wt% of the initiator (i.e., Part 1 initiator) are mixed evenly to obtain the initial monomer mixture (M2) containing the initiator. 65 wt% of the initiator (i.e., Part 2 initiator) is added to the remaining monomer mixture (i.e., Part 2 M1) to obtain the batch monomer mixture (M3) containing the initiator. S3. In a three-necked flask, add 100% of the solvent (xylene: n-butanol = 4:1, v / v) based on the weight of the monomer mixture (M1), 0.8% of the chain transfer agent (n-dodecyl mercaptan) based on the weight of the monomer mixture (M1), and the initial monomer mixture (M2). Stir and purge with nitrogen for 20 min. Simultaneously, under nitrogen protection, control the first reaction temperature at 90°C and react for 20 min. After the first reaction, divide the batch monomer mixture (M3) into 10 equal portions, adding one portion at 15-minute intervals, controlling the reaction temperature at 90°C and reacting for 15 min. Then, add the remaining initiator (i.e., the third initiator) in two equal portions and react at 100°C for 3 h to obtain a light yellow, transparent, and viscous acrylic prepolymer. S4. Under nitrogen protection, the acrylic prepolymer is cooled to below 70°C, and then benzoic acid and zinc oxide are added; the molar ratio of zinc oxide and benzoic acid is 1:1; the total molar amount of zinc oxide and benzoic acid is 1 times the molar amount of acrylic acid; then a mixed solvent (xylene: n-butanol: butyl acetate = 4.4:1:10.6, v / v / v) equal to the total weight of zinc oxide and benzoic acid is added, mixed evenly, and reacted at 110°C for 4 hours. Then the temperature is raised to the azeotropic temperature for dehydration until no distilled water is discharged, and the main chain polysiloxane-zinc acrylate resin is obtained, with the general structural formula as shown in formula (1): (1); In the formula, the general structural formula of M is: ; In the formula, x, y, z, l, m, n, and i are all integers, x = 100~500, y = 50~500, z = 100~1000, l = 50~300, m = 0~50, n = 20~200, and i = 50~5000; Y represents an organic acid, which is one of benzoic acid, rosin, or naphthenic acid.

[0067] The structural characterization of the obtained main-chain polysiloxane-zinc acrylate resin is as follows: Figure 1-8 As shown, from Figure 1 It can be seen from this that 800 cm -1 A significant absorption peak was observed at [value missing], which is attributed to the Si–C stretching vibration mode formed after the addition reaction of terminal vinyl silicone oil with carbon-carbon double bonds, directly confirming the successful copolymerization of terminal vinyl silicone oil and carbon-carbon double bonds. A peak at 1608 cm⁻¹ was also observed. -1 The characteristic peak corresponds to the zinc carboxylate stretching vibration in the Zn(COO-)2 structure generated by the reaction of zinc oxide with prepolymer and organic acid, which provides strong evidence for the formation of zinc acrylate structure.

[0068] Furthermore, thermogravimetric analysis of the vinyl-terminated silicone oil-modified acylmorpholinoacrylate zinc resin revealed that ( Figure 2 Because polysiloxane structures possess excellent thermal stability, they are not easily decomposed at high temperatures. Therefore, as the content of vinyl-terminated silicone oil increases, the thermal decomposition rate of zinc resin gradually decreases, and its thermal stability tends to improve.

[0069] To deeply analyze the chemical composition and bonding characteristics of the resin, XPS technology was used for elemental analysis and chemical state characterization. Azithiocyanate zinc acrylate resin modified with 5 wt% VDV100 was used as an example for XPS characterization. The XPS full spectrum showed that the contents of Si and Zn elements in the resin were 24.15% and 0.06%, respectively, indicating that the resin system contains certain polysiloxane and zinc ion structures. The fine C1s spectrum showed that the characteristic peak at 284.78 eV corresponds to the C–C bond in the main chain; the peaks at 286.58 eV and 288.78 eV belong to the C–O and C=O functional groups in the acrylate, respectively. The O1s spectrum showed a bimodal structure at 531.98 eV and 533.48 eV, corresponding to the C–O and carbonyl C=O bonding states in the ester group, respectively. The Si2p spectrum showed a single characteristic peak at 102.08 eV, confirming the successful introduction of the Si-O structure into the vinyl-terminated silicone oil. The Zn2p spectrum exhibits a characteristic double peak at 1022.38 eV (Zn 2p3 / 2) and 1045.38 eV (Zn 2p1 / 2), and the binding energy positions are consistent with the typical values ​​of Zn(COO–)2 and ZnO, indicating that zinc exists in the resin system in a chemically bonded form. However, due to the low zinc oxide content, the signal is weak.

[0070] The combined results of TGA, ATR-IR, and XPS analyses confirm that Si–C and C–C main chain structures were successfully constructed in the target product, that the end vinyl silicone oil successfully participated in the free radical polymerization of acrylate monomers, and that zinc element exists stably in the side chain structure of the linear polymer in the form of carboxylate. These characterization data corroborate each other and fully reveal the molecular structural characteristics of the resin.

[0071] Example 2 Similar to Example 1, except that the content of terminal vinyl silicone oil (VDV100) in step S1 of Example 1 is replaced with 10 wt%, that is, the amount of terminal vinyl silicone oil added is 10 wt% of the total mass of the mixed monomers.

[0072] Example 3 Similar to Example 1, except that the content of terminal vinyl silicone oil (VDV100) in step S1 of Example 1 is replaced with 20 wt%, that is, the amount of terminal vinyl silicone oil added is 20 wt% of the total mass of the mixed monomers.

[0073] Example 4 Similar to Example 1, except that the content of terminal vinyl silicone oil (VDV100) in step S1 of Example 1 is replaced with 40 wt%, that is, the amount of terminal vinyl silicone oil added is 40 wt% of the total mass of the mixed monomers.

[0074] Comparative Example This comparative example is zinc acrylate resin without added vinyl-terminated silicone oil (VDV100). The preparation method is the same as in Example 1, except that the content of vinyl-terminated silicone oil in step S1 of Example 1 is replaced with 0 wt%.

[0075] Preparation Example The main-chain polysiloxane-zinc acrylate resins prepared in comparative examples and Examples 1-4 were coated onto ABS plastic sheets of 8cm × 10cm and 10cm × 25cm and PVC sheets of 30cm × 90cm respectively to form a coating with a thickness of 400 μm. The coatings were then naturally air-dried at 25°C for 48 hours.

[0076] Application Example 1 The coatings prepared from the main-chain polysiloxane-zinc acrylate resins of Comparative Examples 1-4 were immersed in natural seawater for 5 weeks, and the rate of change in coating mass was tested weekly. The results are as follows: Figure 9 As shown in Table 1-2.

[0077] Acrylonitrile-butadiene-styrene (ABS) sheets measuring 8 cm × 10 cm were cleaned with ethanol, dried, and weighed (W0). Different contents of VDV100-Zn resin were coated onto the ABS sheets, allowed to evaporate naturally for 48 hours, and then dried in an oven at 40°C for 48 hours. The weight of each coated ABS sheet was recorded as W. t The samples were immersed in real seawater, removed every seven days, rinsed with deionized water, and then dried in a 40°C oven for 48 hours. This cycle was repeated for 35 days. The mass of the sample was accurately recorded after each drying process, denoted as W. i The percentage of the remaining mass of the coating after immersion weight loss (W) is calculated using formula (1). s This is used as a key indicator to assess the hydrolysis of the coating, and it can intuitively show the quality changes of the coating caused by hydrolysis during the immersion process from a quantitative perspective, providing data support for evaluating the hydrolytic stability of the coating.

[0078]

[0079] Quality loss rate = W S(i-7) - W Si (i=7, 14, 21, 28, 35) (2) Table 1. Changes in mass loss of the coating after immersion in natural seawater for 35 days.

[0080] Table 2. Total mass loss of the coating after immersion in natural seawater for 35 days.

[0081] The results showed that the total mass loss of the coatings prepared by the main-chain polysiloxane-zinc acrylate resin in Examples 1-4 was less than that of the comparative example (10.33%) over 35 days. Among them, when the content of the vinyl-terminated silicone oil VDV100 was 10wt%, the coating had the smallest mass loss within 5 weeks, and its self-polishing rate was 40% lower than that of the comparative example.

[0082] Application Example 2 The coatings prepared from the main-chain polysiloxane-zinc acrylate resins of the comparative examples and Examples 1-4 were immersed in natural seawater for 7 days. The surface morphology was observed and the roughness change was measured. The results are as follows: Figure 10 And as shown in Table 3.

[0083] Table 3. Surface morphology changes and roughness results of the coating after immersion in natural seawater for 7 days.

[0084] The results showed that when the content of the vinyl-terminated silicone oil VDV100 was 10wt%, the coating surface was the smoothest and the roughest after 7 days of soaking, and no phase separation was observed.

[0085] Application Example 3 The coatings prepared from the main-chain polysiloxane-zinc acrylate resin of the comparative examples and Examples 1-4 were placed at a depth of 2 meters on a real-sea floating raft antifouling test platform. The test area was the Yellow Sea off Qingdao, and the test period was from December 19, 2024 to September 19, 2025. The inhibitory effect of the coatings on marine fouling organisms was evaluated. The results are as follows: Figure 11 As shown in Table 4.

[0086] Table 4. Inhibition effect of coatings on marine fouling organisms.

[0087] Figure captions: +++++ indicates no fouling biofilm (excellent); ++++ indicates only sludge adhesion and a small amount of biofilm (good); +++ indicates only; indicates only some large fouling biofilm (good); ++ indicates 80% of the area has large fouling biofilm and partial coating detachment (poor); + indicates 100% has large fouling biofilm or complete coating detachment (poor).

[0088] The results showed that during the 270-day immersion test, the coating effectively inhibited the adhesion and growth of contaminants on the surface due to its self-polishing behavior. The inhibition effect was optimal when the content of the vinyl-terminated silicone oil VDV100 was 5-10 wt%.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the scope of the present invention should be included within the protection scope of the present invention.

Claims

1. A main-chain polysiloxane-acrylate metal salt resin, characterized in that, Its general structural formula is shown in formula (I): (I); In the formula, the general structural formula of M is shown in formula (II): (II); R1 is H or CH3; R2 is -C4H8N, -C5H9O, -C6H 13 O2、‐C7H 13 -C8H9O or -C 10 H 17 ; R3 is -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -CH2CH(CH3)2, -C(CH3)3, -CH2CH2OH, -CH2CH(CH3)OH, -(CH2)3CH3, -(CH2)4CH3, -(CH2)5CH3, -(CH2)6CH3, -(CH2)7CH3, -(CH2)8CH3, (CH2)9CH3, (CH2) 10 CH3, (CH2) 11 CH3, C8H 17 or (CH2) 17 CH3; R4 is H or CH3; X is a Zn, Cu, Fe, Ca, or Mg metal ion; R5 is the anion of benzoic acid, naphthenic acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, rosin acid, proline, leucine, phenylalanine or arginine, dimer rosin acid, disproportionated rosin acid, salicylic acid or p-chlorobenzoic acid. R6 is H or CH3; x, y, z, l, and i are all integers, where x = 100~500, y = 50~500, z = 100~1000, l = 50~300, and i = 50~5000.

2. The main-chain polysiloxane-acrylate metal salt resin according to claim 1, characterized in that, Its general structural formula is shown in equation (1): (1); In the formula, x, y, z, l, m, and n are all integers, x = 100~500, y = 50~500, z = 100~1000, l = 50~300, m = 0~50, and n = 20~200; Y represents an organic acid, which is one of benzoic acid, rosin, or naphthenic acid.

3. The method for preparing the main-chain polysiloxane-acrylate metal salt resin according to claim 1 or 2, characterized in that, Includes the following steps: S1. Mix acrylate base monomers, acrylic acid, methacrylic acid, acrylamide, and functional acrylate monomers in a molar ratio of (50-150):(0-50):(0-40):(0-40):(1-10); then add 5%-40% of the total mass of the above monomers to prepare monomer mixture M1; subsequently, weigh 0.8%-3.2% of the initiator based on the weight of the monomer mixture for later use. S2. The monomer mixture M1 is divided into two parts, namely the first part M1 and the second part M1. The initiator is divided into three parts, namely the first part initiator, the second part initiator, and the third part initiator. The first part M1 and the first part initiator are mixed to obtain the monomer mixture M2. The second part M1 and the second part initiator are mixed to obtain the monomer mixture M3. S3. In a protective gas atmosphere, monomer mixture M2, monomer mixture M3, the third part initiator, chain transfer agent and solvent are reacted to obtain acrylic acid prepolymer; S4. In a protective gas atmosphere, acrylic prepolymer, metal compound, organic acid and solvent are mixed and reacted to obtain main-chain polysiloxane-acrylate metal salt self-polishing resin.

4. The method for preparing the main-chain polysiloxane-acrylate metal salt resin according to claim 2, characterized in that, In step S1, the acrylate base monomer is one or more of butyl acrylate, ethyl acrylate, methyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate. The functional acrylate monomers are one or more of 4-acrylomorpholine, isobornyl acrylate, cyclohexyl methacrylate, tetrahydrofurfuryl acrylate, ethoxyethoxyethyl acrylate and 2-phenoxyethyl acrylate. The viscosity of the vinyl-terminated silicone oil is 30–10000 mPa·s; The initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, tert-butyl peroxide, methyl ethyl ketone peroxide, ammonium persulfate, and potassium persulfate.

5. The method for preparing the main-chain polysiloxane-acrylate metal salt resin according to claim 2, characterized in that, In steps S2 and S3, the first part M1 accounts for 10% to 30% of the total mass of M1; the total mass ratio of the first part initiator, the second part initiator and the third part initiator to the mass of M1 is 0.8 to 3.2:100; the first part initiator accounts for 15% to 30% of the total mass of the initiator, and the second part initiator accounts for 50% to 70% of the total mass of the initiator.

6. The method for preparing the main-chain polysiloxane-acrylate metal salt resin according to claim 2, characterized in that, In step S3, the monomer mixture M2, chain transfer agent and solvent are mixed and reacted for the first time to obtain the first reaction product. The first reaction product is then mixed with the monomer mixture M3 and reacted for the second time to obtain the second reaction product. Finally, the second reaction product is mixed with the third initiator and reacted for the third time to obtain the main-chain polysiloxane-acrylic acid prepolymer.

7. The method for preparing the main-chain polysiloxane-acrylate metal salt resin according to claim 6, characterized in that, In step S3, the mass ratio of solvent, chain transfer agent, and M1 is (75~150):(0.3~2):100; the temperature of the first reaction is 75~110℃, and the reaction time is 15~45 min; the temperature of the second reaction is 80~95℃; the temperature of the third reaction is 80~95℃, and the reaction time is 2.5~3.5 h. In step S3, during the second reaction, M3 is divided into 9 to 19 portions, with one portion added at 10 to 30-minute intervals. After the addition is complete, the reaction is allowed to proceed for 10 to 30 minutes.

8. The method for preparing the main-chain polysiloxane-acrylate metal salt resin according to claim 2, characterized in that, In step S3, the chain transfer agent is one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, and aliphatic thiols; In step S4, the metal compound is one or more of zinc oxide, copper oxide, magnesium oxide, calcium oxide, zinc hydroxide, copper hydroxide, iron hydroxide, magnesium hydroxide, and calcium hydroxide; the organic acid is one or more of benzoic acid, naphthenic acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, rosin acid, proline, leucine, phenylalanine, arginine, dimer rosin acid, disproportionated rosin acid, salicylic acid, furoic acid, and p-chlorobenzoic acid. In steps S3 and S4, the protective gas is selected from any one of nitrogen, argon, helium, and neon; the solvent is selected from one or more of toluene, xylene, n-butanol, butyl acetate, ethyl acetate, cyclohexanone, and methyl isobutyl ketone.

9. The method for preparing the main-chain polysiloxane-acrylate metal salt resin according to claim 2, characterized in that, In step S4, the molar ratio of the metal compound to the organic acid is 0.5 to 1:1; the total molar amount of the metal compound and the organic acid is 1 to 2 times the total molar amount of acrylic acid and methacrylic acid in step S1; the mass ratio of the total mass of the metal compound and the organic acid to the mass of the solvent is 1:1 to 2; the reaction temperature is 75 to 110°C, and the reaction time is 3 to 10 hours.

10. The application of the main-chain polysiloxane-acrylic metal salt resin according to claim 1 in marine antifouling.